Sternocleidomastoid Syndrome in a Collegiate Basketball Athlete: A Case Study - Sara Stiltner; Rob Whitehurst; Eric Avers (Journal of Sports Medicine and Allied Health Sciences: Official Journal of the Ohio Athletic Trainers' Association)
BACKGROUND: 20-year-old male basketball athlete with recurring upper and lower extremity instability injuries presented fall 2021 with shoulder and ankle instability. A past medical history of thermal capsulorrhaphy from high school with surgical intervention May 2021 (college first year). October 2021 athlete began experiencing rotator cuff strains in both shoulders. November 2021, December 2021, January 2022 athlete experiences recurrent right ankle sprains. Each ankle sprain resulted in two weeks of lost participation, followed by one week of active participation. The third ankle sprain associated with increased swelling and pain over medial ankle. Upon referral and MRI a deltoid ligament sprain and syndesmotic ankle sprain were revealed. Due to time missed for injury athlete received a medical red shirt, returning to activity summer 2022 without incident until October when they experienced a left lateral sprain. Highmark Brain EQ Balance Assessment showed significant impairment and prompted further investigation into the recurrent sprains of both UE and LE. Additionally, the athlete began reporting rib subluxations in October 2022.